(untitled) (Global Journal of Human-Social Science, 2023)
Researchers on LGBTQ individuals have largely focused on lesbians or gay men bisexual individuals often are included in those samples but they are seldom differentiated in reporting Little is known therefore about the lived experience of bisexual individuals especially women of color who represent three marginalized groups i e LGBTQ women racial ethnic minoritized individuals In this phenomenological study we explored the lives of 12 selfidentified bisexual women of color aged 18 to 33 Three phenomena described the essence of their experiences a forming sexual identity b making decisions about how to share personal information and c acknowledging the positive consequences of identities Findings highlight the simultaneous interpretation of experiences as challenges and positives for bisexual women of color The ambiguity and ambivalence associated with being a member of multiple minoritized groups and implications for better serving and understanding individuals with multiple marginalized identities are discussed